Tillage and Seed Rate Impact on Wheat Yield, Soil Organic Matter and Total Soil Nitrogen under Rice-Wheat Cropping System in Northwestern Pakistan - Usman, Khalid; Khan, Said Mir; Awan, Inayatullah; Ghulam, Said; Khan, Muhammad Umar; Khan, Muhammad Anwar; Rehman, Aziz ur (2012)
Conservation tillage practices with an appropriate seed rate recover the declining wheat (Triticum aestivum L.) yield and soil quality using conventional tillage in poorly drained silty clay soil (calcareous, hyperthermic and Typic Torrifluvents) in rice-wheat cropping system. Field experiments were conducted for 2 consecutive yr to study the impact of three tillage techniques [zero (ZT), reduced (RT) and conventional tillage (CT)] and four seed rates viz. 70, 100, 130 and 160 kg ha-1 on wheat yield, soil organic matter and total soil nitrogen in rice-wheat cropping system in northwestern Pakistan. Mean values for tillage revealed that conservation tillage (ZT and RT) resulted in higher spikes per m2, biological yield, grain yield, soil organic matter and total soil nitrogen compared with CT. Mean values for seed rates displayed the highest yield and yield components at 130 kg ha-1 and showed the lowest values at 70 kg ha-1 seed rate. The results revealed that ZT / RT in combination with 130 kg ha-1 seed rate produced higher grain yield compared with CT in the first growing season. In contrast, CT in combination with 130 kg ha-1 seed rate gave the highest grain yield in the second growing season. The results emphasized the necessity of using 130 kg ha-1 seed rate in ZT for improving soil organic matter and total soil nitrogen, and sustaining wheat yield in poorly drained silty clay soil. However, in case of severe infestation with weeds or insect pests, CT in combination with 130 kg ha-1 seed rate may be the best alternative.
Keywords: Wheat--Yields.; Soil composition